NILAI RELIGIUS DAN KEBERSAMAAN SOSIAL DALAM RITUAL ROKAT TASE’ MASYARAKAT MADURA - Aminuddin, Fajrian (Muta'allim: Jurnal Pendidikan Agama Islam, 2024)
This research aims to explore the Madurese culture of Rokat Tase' and its relationship with the religious socialism of the community. This research will discuss the relationship between social and tradition, its influence in the community environment and the involvement of religious factors in it. The results of this research will show that the Rokat Tase' cultural tradition carried out by the Madurese community, especially in coastal areas, has a strong socio-religious value among the community. Rokat Tase' is a form of community representation as a form of gratitude for the abundant sea products, wanting to get safety from calamities and be given a smooth sustenance. This article will also reveal some forms of socialism and religion of the community as a form of implementation of this Rokat Tase' culture